Oral microbiome dysbiosis is associated with chronic respiratory diseases: evidence from a population-based study and a hospital cohort - Jia, Baolin; Wu, Xiaojuan; He, Gaoyan; Wang, Qiang; Guan, Li; Ren, Jun; Li, Guixin; Zheng, Xianjie; Yang, Sen (Frontiers in Public Health, 2025)
BackgroundThe oral microbiome has been increasingly recognized for its role in systemic health through the oral–lung axis. However, population-level evidence linking oral microbial diversity and composition with chronic respiratory diseases (CRD) remains limited.MethodsWe analyzed data from 4,384 adults in the 2009–2012 National Health and Nutrition Examination Survey (NHANES), defining CRD by self-reported chronic obstructive pulmonary disease (COPD), asthma, emphysema, or chronic bronchitis. Oral rinse samples underwent 16S ribosomal RNA (16S rRNA) V1–V3 sequencing. Alpha diversity, including observed amplicon sequence variants (ASVs), Faith’s phylogenetic diversity (Faith’s PD), Shannon–Weiner index, and Simpson index, and beta diversity, including Bray–Curtis, weighted UniFrac, and unweighted UniFrac distances, were assessed. Associations with CRD were examined using weighted logistic regression and restricted cubic splines (RCS). Differential genus abundance was identified by Wilcoxon tests with false discovery rate correction. A random forest model integrated microbial and clinical features. An independent hospital cohort was additionally profiled by 16S rRNA sequencing, and genus-level differences were assessed with linear discriminant analysis effect size (LEfSe) to validate NHANES findings.ResultsHigher alpha diversity was inversely associated with CRD risk; each standard deviation increase in observed ASVs and Faith’s PD reduced CRD odds by 19 and 17%, respectively (p < 0.05). Beta diversity showed significant community-level separation by CRD status (p = 0.01). Several genera, including Rothia and Veillonella, were enriched in CRD, whereas Prevotella, Haemophilus, and Neisseria were more abundant in non-CRD individuals. The random forest model achieved an area under the curve (AUC) of 0.65. In the hospital cohort, compositional shifts were consistent with NHANES findings, and LEfSe confirmed the depletion of Alloprevotella and Peptostreptococcus in CRD patients.ConclusionOral microbial diversity and composition were significantly associated with CRD across both a representative U. S. population and a hospital cohort. Select genera and diversity indices may serve as non-invasive biomarkers for respiratory health, warranting further validation in longitudinal and mechanistic studies.